Nepal-India Relations: Exploring the Dichotomy between ’Big Brother’ and ’Brotherhood’ - Ghimire, Bhesh Raj (NPRC Journal of Multidisciplinary Research, 2024)
The historical relationship between Nepal and India is deeply rooted in their geographic proximity and shared elements such as religion, culture, language, and socio-economic interests. While Nepal borders both China and India, its closeness with India is accentuated by these shared attributes and mutual opportunities. The two countries share an open border of around 1,780 kilometers along Nepal's eastern, western, and southern regions. Despite India's larger size, population, and more advanced economic development, Nepal maintains its sovereignty and equal status as an independent nation. However, India's role is often perceived as that of a "big brother" to Nepal, reflecting the disparity in size and influence. Nonetheless, all sovereign nations, regardless of their geographic or economic differences, are regarded as equals in status. In an era defined by globalization, scientific advancements, and technological progress, Nepal aspires to build a strong relationship with India based on mutual friendship and economic cooperation, particularly through foreign investment and the exchange of technology. While occasional tensions arise, usually from the Indian side, they have not escalated into major conflicts and are unlikely to do so. It is widely understood that while friendships may fluctuate, the bond between neighbors remains constant. This article examines the various aspects and dynamics of Nepal-India relations within this context.